An Approach to Asset Pricing Under Incomplete and Diverse Perceptions - Eyster, Erik; Piccione, Michele (Econometrica, 2013)
We model a dynamic, competitive market, where in every period, risk-neutral traders trade a one-period bond against an infinitely lived asset, with limited short-selling of the long-term asset. Traders lack structural knowledge and use different “incomplete theories,” all of which give statistically correct beliefs about next period's market price of the long-term asset. The more theories there are in the market, the higher is the equilibrium price of the long-term asset. Investors with more complete theories do not necessarily earn higher returns than those with less complete ones, who can earn above the risk-free rate. We provide two necessary conditions for a trader to earn above the risk-free rate.